مساهمة توصيات لجنة بازل Iii في الحد من مخاطر السيولة للمصارف - عزوز, ميلود; سعيدي, عبد الحليم (جامعة الوادي - University of Eloued, 2022)
تهدف لجنة بازل بشكل عام منذ إنشائها إلى خلق تعاون ما بين الدول الأعضاء في مجال الرقابة، فهي تعمل على المستوى الدولي من اجل تعزيز نوعية وفعالية الرقابة البنكية وذلك من خلال ثلاثة محاور للتدخل هي: تبادل المعلومات حول ممارسات الرقابة؛ تحسين فعالية التقنيات المستخدمة في مراقبة الأنشطة البنكية العالمية؛ تحديد المعايير الاحترازية الدنيا للمصارف. وتوصلت الدراسة الى ان التعديلات التي جاءت بها اتفاقية بازل الثالثة استنبطت من دروس الأزمة المالية، وتهدف لتحصين المراكز المالية للمصارف وحمايتها من أزمات مالية جديدة، كما توصلنا الى أن إدارة المخاطر المصرفية هي عملية تحديد وقياس وتقييم المخاطر التي يتعرض لها المصرف وكذا إعداد الخطط لتجنبها أو التقليل منها. وبالتالي نوصي بالالتزام باتفاقية بازل 3 على مستوى المصارف وذلك من خلال التطبيق الفعلي لمعايير بازل الثالثة، بالإضافة إلى تدعيم القانون والتشريع المصرفي من جهة، والتأكد على دورها في إدارة المخاطر المصرفية من جهة أخرى، وكذا نشر الوعي الثقافي لموظفين البنك للتعرف على أهمية المخاطر المصرفية في البنك وكيفية استخدام تقنياتها. The Basel Committee, in general, since its establishment, aims to create cooperation among member states in the field of supervision. It works at the international level to enhance the quality and effectiveness of banking supervision through three axes of intervention: exchanging information about oversight practices; Improving the effectiveness of techniques used to monitor global banking activities; Determining the minimum precautionary standards for banks. The study concluded that the amendments brought by the Basel III agreement were drawn from the lessons of the financial crisis, and aim to fortify the financial positions of banks and protect them from new financial crises, reduce them. Therefore, we recommend adhering to the Basel III Convention at the level of banks through the actual application of Basel III standards, in addition to strengthening banking law and legislation on the one hand, and ensuring its role in banking risk management on the other hand, as well as spreading cultural awareness for bank employees to learn about the importance of banking risks in Bank and how to usetheir techniques.
The contribution of Basel III committee recommendations to reducing liquidity risk for banks
مقال
Keywords: بازل III، المخاطر المصرفية، مخاطر السيولة.; Basel III, banking risk, liquidity risk